Pengaruh Pemanfaatan Teknologi Informasi, Kualitas Sistem Informasi Akuntansi dan Kompetensi SDM Terhadap Kualitas Laporan Keuangan - Beta Vemi Aprilia; Robinson (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research goals to analyze the influence of Information Technology Utilization, Accounting Information System Quality, Human Resources (HR) Competency on the Quality of Financial Reports in the Bengkulu City Regional Government. The method applied was qualitative using primary data, as well as purposive sampling techniques involving 62 respondents, consisting of Financial Administration Officials (PPK), treasurers, and administrative staff at the Regional Apparatus Work Unit (SKPD). The data was examined through multiple linear regression via the SMART PLS software. Findings reveal that the three independent variables greatly impact the quality of financial documentation. The integration of Information Technology has been proven to increase the efficiency, accuracy, transparency of financial management. The quality of the Accounting Information System supports systematic and timely financial recording and reporting. Meanwhile, HR Competency takes part in improving the reliability and accuracy of financial statements through understanding government accounting standards and system operational capabilities. Simultaneously, the three variables were able to explain 38.4% of the variation in the quality of financial statements. These findings suggest that these factors have a considerable contribution to improving the quality of local government financial reporting, although there is still room for further research considering other variables that may be relevant.